2016
DOI: 10.1007/s12291-016-0621-6
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Aqueous Garlic Extract on Inflammation and Oxidative Stress Status in the Kidneys of Type 1 Diabetic Rats

Abstract: One of the most important complications of diabetes is nephropathy. This study investigates the effects of aqueous garlic extract on inflammation and oxidative stress status in the kidneys of diabetic rats. Male rats were divided into four groups- control rats, diabetic rats, garlic extract-treated diabetic rats, garlic extract-treated normal rats. The glucose, urea, uric acid, and creatinine levels were measured in sera using colorimetric methods. To determine the oxidative stress condition in the kidney tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…In the kidney of healthy animals, TAC was not affected by the administration of crocin. This result agrees with Nasiri et al [44], who reported that the administration of antioxidant compounds did not affect renal TAC in healthy animals. The induction of diabetes did not have any significant impact either.…”
Section: Discussionsupporting
confidence: 93%
“…In the kidney of healthy animals, TAC was not affected by the administration of crocin. This result agrees with Nasiri et al [44], who reported that the administration of antioxidant compounds did not affect renal TAC in healthy animals. The induction of diabetes did not have any significant impact either.…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative stress appears as important factor that leads cells to severe damages and diseases [12]. Oxidative stress and lipid peroxidation due to increased free radicals of oxygen play a key role in the damage of the kidney tissue in diabetic patients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A sativum and O vulgare are also antimicrobial. 28 , 29 , 30 , 31 , 32 , 33 However, only research exists that demonstrates that A sativum is antiviral while the antiviral effects of O vulgare in the research is largely unknown. 18 , 26 , 33 Consequently, the combined immunostimulatory and antioxidant functions of zinc, Emergen-C, O vulgare , and A sativum in conjunction with the antiviral activity of A sativum should have reduced the severity of her illness and her symptoms .…”
Section: Discussionmentioning
confidence: 99%